PENGAMANAN AUTENTIKASI SISTEM INFORMASI AKADEMIK ENGGUNAKAN KRIPTOGRAFI ONE TIME PAD - Iqbal Adhi Surachman, - (2019)
Academic information system is built to provide convenience to the students in their educational administration activities online. Each academic information system must have its own security system, but in its security must have a weakness. One of the problems encountered in the security of academic information systems is how the system can ensure that users who access data or information on the system are truly authorized users. This research is done to add security to academic information system that is with cryptography one time pad this process log in will in first authentication by sending a key to account owner SIAKAD so owner will pass 2 stages in login to academic information system